Dietary Asafoetida (Ferula Asafetida) - Nargiza R. Hamzaeva; Nozigul Kiyamova; IrodaYa. Sattarova; Malika Ruzibayeva; Dinara I. Muzrapova (International Journal on Human-Computing Studies, 2021)
Ferula asafoetida is a strong, durable and sulfur-smelling oleo-gum resin with medicinal and nutritional value. Asafoetida has been consumed as a spice and folk medicine for centuries. Recent studies have identified a number of promising activities, including antioxidant, neuroprotective, memory enhancing, digestive enzyme, antioxidant, antispasmodic, hypotensive, hepatoprotective, antimicrobial, anticarcinogen, anticancer, antitoxic, antiobesitic, andanthelmic. This review deals effectively with various pharmacological and clinical studies of phytochemistry and asafoetida.